2019
DOI: 10.1021/acsomega.8b03369
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Properties of Iron-Doped Porous Graphitic Carbon Synthesized by Hydrothermal Carbonization of Cellulose and Subsequent Pyrolysis

Abstract: The applied pyrolysis temperature was found to strongly affect composition, structure, and oxidation behavior of pure and iron oxide nanoparticle (NP)-loaded carbon materials originating from hydrothermal carbonization (HTC) of cellulose. A strong loss of functional groups during pyrolysis at temperatures beyond 300 °C of the HTC-derived hydrochars was observed, resulting in an increase of the carbon content up to 95 wt% for the carbon materials pyrolyzed at 800 °C and an increase of the specific surface area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…In addition, Wan et al showed that by pyrolyzing the BC/Fe 2 O 3 aerogel at 600 °C in N 2 , the reduced atmosphere transforms the aerogel to a CNF/Fe 3 O 4 composite . Similarly, the conversion of iron oxides (Fe 2 O 3 and Fe 3 O 4 ) to metallic iron in the presence of cellulose has been observed in the pyrolysis temperature range of 600–800 °C. , This is analogous to a smelting process where iron is extracted from iron ore in the presence of carbon. In this case, the carbon source is the bacterial cellulose fibers.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, Wan et al showed that by pyrolyzing the BC/Fe 2 O 3 aerogel at 600 °C in N 2 , the reduced atmosphere transforms the aerogel to a CNF/Fe 3 O 4 composite . Similarly, the conversion of iron oxides (Fe 2 O 3 and Fe 3 O 4 ) to metallic iron in the presence of cellulose has been observed in the pyrolysis temperature range of 600–800 °C. , This is analogous to a smelting process where iron is extracted from iron ore in the presence of carbon. In this case, the carbon source is the bacterial cellulose fibers.…”
Section: Resultsmentioning
confidence: 97%
“…41 Similarly, the conversion of iron oxides (Fe 2 O 3 and Fe 3 O 4 ) to metallic iron in the presence of cellulose has been observed in the pyrolysis temperature range of 600−800 °C. 54,55 This is analogous to a smelting process where iron is extracted from iron ore in the presence of carbon. In this case, the carbon source is the bacterial cellulose fibers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…11 The organic precursors also vary widely, and include small molecules such as sucrose, 12 polymeric species such as phenolic resins, 13 pure cellulose, 14 raw biomass, 15,16 or biomass-derived hydrochars. 17 Depending on the precursors and conditions, catalytic graphitization has produced various graphitic nanostructures such as hollow 'shells', 18 nanotubes 19 and nanoribbons. 11 The mechanism of formation of these nanostructures is generally agreed to proceed via in situ formation of Fe 3 C nanoparticles, which catalyze the conversion of amorphous carbon to graphitic carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Different quantities of ashes are also present in non-negligible amounts. The carbon content in char usually ranges between 65 and 95 wt%, depending on the initial biomass composition and pyrolysis operating conditions, while the hydrogen and oxygen content progressively drops as the pyrolysis temperature rises. , The content of H and O directly influences the rate of char conversion during oxidation and gasification. , Due to the large amounts of volatile matter present in biomass (usually around 60–85 wt%), the resulting biochars are significantly porous, thus strongly influencing the intrinsic surface area. This, combined with the high content of hydrogen and oxygen, results in a considerably higher reactivity in combustion/gasification conditions when compared with coal chars. , …”
Section: Introductionmentioning
confidence: 99%